Electronic voting : 5th International Joint Conference, E-Vote-ID 2020, Bregenz, Austria, October 6-9, 2020, proceedings /: 5th International Joint Conference, E-Vote-ID 2020, Bregenz, Austria, October 6-9, 2020, proceedings. (2020) - Unknown
No abstract available